The Effects of Using Blended Learning on the Development of 21st Century Skills for Female Eleventh Grade Students of Islamic Education Course - Al-saqri, Rabaa Mohammed (Dirasat: Educational Sciences, 2020)
The aim of this study is to identify the effect of using blended learning on developing some of the 21st century skills of female eleventh grade students of Islamic Education course. The study used a quasi experimental design, with a sample of 60 female students. The sample was further divided into two groups; namely, experimental (29), and control (31). To achieve the objectives of the study, a 21st Century skills scale was prepared. It consisted of (42) items distributed into two domains. The content validity was checked by a group of referees, and reliability coefficient was (0.85). A creative thinking and a critical thinking tests were implemented in this study and the validity of these tests was also conducted through a panel of judges, while the reliability was calculated using Cronbach Alpha which reached (0.78) and (0.65), respectively. The results indicated that the experimental group outperformed the controlled group in both the 21st Century skills scale and creative thinking. The results also revealed that there were no statistically significant differences in critical thinking test results. The study recommended using blended learning in teaching Islamic Education course because of its effectiveness in developing 21st century skills.